Can SNOMED CT as Implemented in New South Wales, Australia Be Used for Road Trauma Injury Surveillance in Emergency Departments?. Issue 2 (June 2013) - Mitchell, Rebecca J.; Bambach, Mike R.; Muscatello, David; McKenzie, Kirsten; Balogh, Zsolt J.
The introduction of Systematized Nomenclature of Medicine - Clinical Terms (SNOMED CT) for diagnosis coding in emergency departments (EDs) in New South Wales (NSW) has implications for injury surveillance abilities. This study aimed to assess the consequences of its introduction, as implemented as part of the ED information system in NSW, for identifying road trauma-related injuries in EDs. It involved a retrospective analysis of road trauma-related injuries identified in linked police, ED and mortality records during March 2007 to December 2009. Of all SNOMED CT codes in the principal provisional diagnosis field, between 53.7% and 78.4% referred to the type of injury or symptom experienced by the individual. Of the road users identified by police, 3.2% of vehicle occupants, 6% of motorcyclists, 10.0% of pedal cyclists and 5.2% of pedestrians were identified using SNOMED CT codes in the principal provisional diagnosis field. The introduction of SNOMED CT may provide flexible terminologies for clinicians. However, unless carefully implemented in information systems, its flexibility can lead to mismatches between the intention and actual use of defined data fields. Choices available in SNOMED CT to indicate symptoms, diagnoses, or injury mechanisms need to be controlled and these three concepts need to be retained in separate data fields to ensure a clear distinction between their classifications in the ED.